2005
DOI: 10.1002/app.21828
|View full text |Cite
|
Sign up to set email alerts
|

Photopolymerization kinetics of dimethacrylate‐based light‐cured dental resins

Abstract: ABSTRACT:The influence of certain factors [structure and concentration of tertiary amines as coinitiators, monomer composition, presence of inorganic pigments, and incident light intensity (I 0 )] on the polymerization rates (R p ), polymerization quantum yields, and conversions of bisphenol A-bis(glycidyl methacrylate) (Bis-GMA)/triethylene glycol dimethacrylate based resins was studied. The initial rate of bulk polymerization increased and the final conversion decreased with the content of Bis-GMA in the mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 20 publications
5
26
1
Order By: Relevance
“…CQ produces free radicals on exposure to 450-500 nm radiation and this process is activated by the redox reaction with tertiary amines. [1][2][3][4][5][6] CQ is the most common photoinitiator but it possesses a noticeable yellowish color. For the majority of restorative work this is not an issue as natural tooth color also has a yellowish hue, but for cosmetic restoration this yellow color can be a significant factor.…”
Section: Introductionmentioning
confidence: 99%
“…CQ produces free radicals on exposure to 450-500 nm radiation and this process is activated by the redox reaction with tertiary amines. [1][2][3][4][5][6] CQ is the most common photoinitiator but it possesses a noticeable yellowish color. For the majority of restorative work this is not an issue as natural tooth color also has a yellowish hue, but for cosmetic restoration this yellow color can be a significant factor.…”
Section: Introductionmentioning
confidence: 99%
“…45,65 It is well-known that absorbance spectra, and thus I abs , depend on the electronic and resonance characteristics of the solvent (confirmed in Figure S3). Hence, obtaining I abs in the actual polymerizing medium provides an unparalleled advantage over other analytical methods.…”
Section: Resultsmentioning
confidence: 81%
“…Otherwise, the materials did not differ statistically among themselves in DC for amine concentrations above 1 mol% (1:2). Previous studies have demonstrated that the efficiency of radical generation has a direct influence on polymerization efficiency [6,8]. These results are related to the fact that sufficient amine is necessary to act as hydrogen donor for CQ and start the polymerization process, but, on the other hand, above certain limits, any amine co-initiator may act as a retarder because an excess of amine may trap initiating radicals by termination reactions [25].…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, factors such as CQ and amine concentrations, their ratio, molecular structure of the amine, and reactivity of the formed radicals to initiate monomer polymerization, all play important roles on the polymerization reaction properties of the resulting polymer [3,6,7]. Although a direct correlation between co-initiator concentration and polymerization efficiency might be considered, it is known that above certain concentration limits, amines may act as retarders since excess amine may trap initiating radicals by termination reactions [6,8]. Excess amine might also cause color instability because of the eventual formation of oxidative products [9][10][11].…”
Section: Introductionmentioning
confidence: 99%